General Publishing Correspondence (M-P) - Evans, Melvin; Swanepoel, Pat; Abrahams, Peter; Mutebi, George; Mile, Van; Walker, Gerald; Polsgrove, Caol; Meyer, Ernst (My University, 2007)
General Publishing Correspondence (M-P) between Peter Abrahams and representatives from publishing houses, as well as individuals
85 pgs. Typescript, letter-sized, sepia-toned, in good condition.
Keywords: Publishers and publishing; Authors and publishers; Book industries and trade